2019
DOI: 10.3389/fnins.2018.01057
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Moxibustion Modulates Sympathoexcitatory Cardiovascular Reflex Responses Through Paraventricular Nucleus

Abstract: Electroacupuncture (EA) point specific (ST36-37) stimulation decreases cardiovascular reflex responses through supraspinal regions such as the hypothalamic paraventricular nucleus (PVN) while mechanical stimulation of acupoints decreases pressor responses through peripheral thermal transient receptor potential vanilloid type-1 (TRPV1). Moxibustion generating heat applied at acupoint in combination with antihypertensive drugs decreases elevated blood pressure. We hypothesized that moxibustion modulates sympatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…TRPV2 can be activated by moxibustion temperature above 52°C to promote the production of active substances, such as growth factors and inflammatory regulatory factors, to produce subsequent effects [ 89 ]. When the moxibustion temperature exceeds 45°C, noxious stimulation will occur, and the harmful sensor of C fiber is activated, resulting in local thermal pain, burning pain, and other sensations and inducing a local burning reaction [ 90 , 91 ]. At this time, the activation of dorsal reticular nucleus neurons in the medulla oblongata related to analgesia was suddenly strengthened, and the analgesic effect of thermal moxibustion was exerted [ 87 ].…”
Section: The Mechanism Of Moxibustionmentioning
confidence: 99%
“…TRPV2 can be activated by moxibustion temperature above 52°C to promote the production of active substances, such as growth factors and inflammatory regulatory factors, to produce subsequent effects [ 89 ]. When the moxibustion temperature exceeds 45°C, noxious stimulation will occur, and the harmful sensor of C fiber is activated, resulting in local thermal pain, burning pain, and other sensations and inducing a local burning reaction [ 90 , 91 ]. At this time, the activation of dorsal reticular nucleus neurons in the medulla oblongata related to analgesia was suddenly strengthened, and the analgesic effect of thermal moxibustion was exerted [ 87 ].…”
Section: The Mechanism Of Moxibustionmentioning
confidence: 99%
“…Acupuncture, a non-pharmacological intervention founded in Traditional Chinese Medicine (TCM), has proven to protect the cardiovascular system by regulating vascular tension, 35 improving myocardial damage, 36 reversing endothelial dysfunction, 37 and regulating lipid metabolism. 20 As an adjuvant therapy, acupuncture has been applied to treat CHD for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Professor Qiufu Ma has proposed that acupuncture effects can be realized through somatosensory-autonomic reflexes, and they found that EA stimulation at ST36 activated the Phox2a projection neurons within the spinal dorsal horn, and the neurons densely project to the NTS ( Ma, 2020 ; Liu et al, 2021b ). Furthermore, studies have highlighted acupuncture alter specific brain regions such as cardiovascular regulation-related paraventricular nucleus (PVN) ( Cheng et al, 2018 ), psychomotor response-related CeA ( Kim et al, 2021 ), and drug dependence-related cuneate nucleus ( Chang et al, 2019 ) and so on, which suggest that acupuncture-evoked brain response. Acupuncture stimulation at different acupoints has been reported to drive different autonomic pathways associated with gastrointestinal-motility control ( Li et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%